SPOSAB ABP 501: A Sicilian Prospective Observational Study of Patients with Inflammatory Bowel Disease Treated with Adalimumab Biosimilar ABP 501. Issue 11 (3rd July 2021) - Macaluso, Fabio Salvatore; Cappello, Maria; Busacca, Anita; Fries, Walter; Viola, Anna; Costantino, Giuseppe; Magnano, Antonio; Vinci, Elisa; Ferracane, Concetta; Privitera, Antonino Carlo; Piccillo, Giovita; Belluardo, Nunzio; et al.
Abstract: Background and Aim: There are few clinical data on Adalimumab (ADA) biosimilars in inflammatory bowel disease. We aimed to perform a multicenter, observational, prospective study on safety and effectiveness of ADA biosimilar ABP 501 in patients with inflammatory bowel disease. Methods: All consecutive patients from the cohort of the Sicilian Network for Inflammatory Bowel Disease treated with ADA biosimilar ABP 501 from February 2019 to February 2020 were enrolled. Patients were divided into three groups: group A, naïve to ADA and naïve to anti‐tumor necrosis factors; group B, naïve to ADA and previously exposed to anti‐tumor necrosis factors; and group C: switched from ADA originator to ABP 501. Results: A total of 559 patients (median age 39 years; Crohn's disease 88.0%, ulcerative colitis 12.0%) were included, with a follow‐up time of 403.4 patient‐years. Thirty‐six serious adverse events occurred in 36 patients (6.4%; incidence rate [IR]: 8.9 per 100 person‐years [PY]). The IR of serious adverse events was higher among patients in group A compared with group C (17.4 vs 4.8 per 100 PY; IR ratio = 3.61; P < 0.001) and among patients in group B compared with group C (16.4 vs 4.8 per 100 PY; IR ratio = 3.42; P = 0.041). Among ADA‐naïve patients (group A + B), 188 (85.8%) had a clinical response after 12 weeks, including 165 (75.3%) who achieved steroid‐free remission. Higher treatment persistence estimates were reported for patients in group C compared with groups A and B (log–rank P < 0.001). Conclusions: Safety and effectiveness of ABP 501 seem to be overall similar to those reported for ADA originator. Switching from originator to ABP 501 was safe and effective.